FEATURES OF MATHEMATICS TEACHING IN SOME DEVELOPED COUNTRIES - Brydun, В. Л.; Pekarska, Я. Т. (Journal of Information Technologies in Education (ITE), 2025)
The article examines approaches to teaching mathematics in developed countries such as the USA, Singapore, Japan and Finland. Since teaching mathematics is an important component of training future engineers, scientists, programmers, analysts, and entrepreneurs, in these countries special attention is paid to the development of analytical and mathematical thinking, solving and modeling practical problems, and the ability to analyze the obtained results. In the USA, the mathematics teaching system is aimed at developing critical thinking and applying knowledge in real life. Considerable attention is paid to the integration of information and communication technologies, ICT, into the educational process and motivating students to learn through project activities. In Finland, known for its consistently high results in international testing (such as PISA), the importance of an individual approach to each student is emphasized. Here, less stress is placed on assessment and more on a deep understanding of the material, cooperation, and the development of the student’s internal motivation. In Japan, the emphasis is on deep mastery of basic mathematical concepts through repeated repetition and variety of exercises. A Japanese mathematics lesson, which Stigler and Hiebert classify as “structured problem solving,” includes five steps: review of the previous lesson, presentation of the problem, individual or group work, discussion with the whole class, and review/summary. In Singapore, which is one of the world leaders in mathematics education, the “conceptual learning” method is used. Students learn not only to perform algorithms, but also to understand why these algorithms work. The main idea is to gradually move from the concrete to the abstract, which ensures a solid assimilation of knowledge. It is extremely important for Ukraine to study and adopt these approaches. In the modern world, where technology and science are becoming the engines of economic development, strong mathematical knowledge is the key to the country’s success. The transition from mechanical mastery of formulae to the development of critical thinking, maintaining interest in learning, integrating the latest technologies, and an individual approach to the student can significantly improve the quality of Ukrainian mathematics education. The introduction of the best global practices will allow us to educate a generation capable of solving complex problems of the future and building a strong economy.